Pengaruh Pemberian Jus Buncis (Phaseolus Vulgaris Linn) terhadap Kadar Malondialdehide Tikus Model Stres Psikologis - Dianti Ias Oktaviasari (Universitas Wijaya Kusuma Surabaya, 2018)
Psychological stress is often suffered by people with body rhythm disorders, one of whom is a person with sleep disorders upside down. Psychological stress can trigger oxidative stress. Oxidative stress can be overcome by increasing antioxidants, beans as antioxidants are considered to reduce oxodative stress. The objective of the study was to examine the effect of green bean juice on the levels of Malondialdehyde (MDA) in male white wistar strains exposed to psychological stress. The design used in this research is Randomized Post Test Only Group Design. There were 5 groups tested, 2 normal and stress control groups, and 3 treatment groups. Exposure to psychological stress with reverse sleep guard pattern, so that the condition of experimental animals experiencing oxidative stress, then given bean juice with a dose of 4.5 gr / 1 ml in the treatment group. The results showed MDA levels dropped in the first hour and remained down until the 24th hour after the provision of bean juice. The effect of antioxidant flavonoids on beans decreases the amount of free radicals by scavenging mechanisms in free radicals and increases levels of endogenous antioxidants and increases insulin levels. The role of arginine in beans acts as a precursor of the formation of Nitric Oxide (NO) as vasodilator of blood vessels so as to decrease oxidative stress. A single dose of bean juice in experimental animals has been shown to overcome oxidative stress due to exposure to psychological stress since the first hour of green bean juice and its antioxidant activity persisted until the 24th hour.